Evaluation of Corrosion Resistance of Alloy 625 Obtained by Laser Powder Bed Fusion. Issue 11 (12th June 2019) - Cabrini, M.; Lorenzi, S.; Testa, C.; Pastore, T.; Brevi, F.; Biamino, S.; Fino, P.; Manfredi, D.; Marchese, G.; Calignano, F.; Scenini, F.
Abstract : The aim of this work is to compare the corrosion resistance of nickel-base Alloy 625 (UNS N06625) produced by laser powder bed fusion with that obtained via conventional casting and hot working. Cyclic potentiodynamic polarization and potentiostatic tests were performed in order to evaluate the corrosion resistance of the differently manufactured alloys according to ASTM G5, and in NaCl 0.6 M solution at pH 7 and pH 3, at 40°C. The electrochemical characterization was carried out on the as-produced alloy and after annealing at 980°C for 32 minutes (according to ASTM B446). This heat treatment was also performed on the commercial hot worked alloy. Two surface conditions, namely as-built and polished surfaces, were investigated on the additive manufactured specimens. The alloy produced by laser powder bed fusion was not susceptible to pitting in the considered environments and had a good localized corrosion resistance, slightly higher than that of traditional wrought material. However, as predicted, the corrosion resistance of the as-built surfaces increased after mechanical polishing. The correlation between the corrosion performance and microstructure is also discussed.